Characterisation of a collection of perennial Panicum species - Wouw, M. van de; Jorge, M.A.B.; Bierwirth, J.; Hanson, Jean (2008)
A collection of 74 perennial Panicum accessions, belonging to 6 different species, maintained at the field genebank of the International Livestock Research Institute, was described using 49 agromorphological characters in a multivariate analysis. Fifty-four accessions, for which coordinates of the collection site were available, were further characterised using environmental data obtained through use of geographic information systems. Three drought-tolerant species, P. antidotale, P. turgidum and P. phragmitoides, were very different agro-morphologically from the other species. Of these drought-tolerant species, P. phragmitoides appeared to have the best agromorphological attributes for use as forage in dry areas. P. maximum, P. coloratum and P. infestum appeared more similar, and were not entirely separated using cluster analysis. The accessions of these 3 species could be divided into 5 different clusters with similar characteristics. The majority of the P. maximum accessions belonged to 2 clusters, mainly differing in the size and robustness of the plants. A strong correlation was found between characters describing the robustness of the P. maximum plant and the annual precipitation at the collection site. Promising P. maximum accessions for use in cut-and-carry systems were identified.